Prevalence and antimicrobial resistance characterization of multidrug-resistant Staphylococcus epidermidis isolated from raw milk of dairy cattle and ewes - Inamullah; Mustafa Kamal; Farhad Badshah; Shehryar Khan; Ghassan Tayh; Mourad Ben Said; Eliana Ibánez-Arancibia; Patricio R. De los Ríos Escalante; Huma Fatima; Muhammad Ikram; Hanène Belkahia; Tahir Usman (PLoS ONE, 2025)
Milk is a vital and widely consumed food, but contamination by biological, chemical, and physical factors can lead to milk-borne diseases. Mastitis, particularly subclinical mastitis (SCM), is a significant biological factor that deteriorates milk quality. Among the 135 agents causing SCM, Staphylococcus epidermidis , a Gram-positive coagulase-negative staphylococcus, plays a notable role. The excessive and indiscriminate use of antibiotics in treating mastitis has led to the emergence of multidrug-resistant (MDR) strains, posing threats to both animal and human health. This study aimed to assess the prevalence of SCM and identify MDR S. epidermidis isolates in raw milk samples from dairy cattle and ewes, and explore the presence of antibiotic resistance genes ( mecA , tetK , and ermC ) in these isolates. A total of 310 milk samples were collected from Holstein Friesian and Cholistani cattle, as well as ewes under transhumant and sedentary husbandry systems. The results revealed a 26% overall prevalence of SCM, with a higher incidence in ewes (31.34%) than in cattle (21.87%). Within cattle, SCM prevalence rate was 40% in the Cholistani breed and 17.69% in the Holstein breed. S. epidermidis was detected in 12.9% of the samples, with 72.5% of these isolated from SCM cases. Antibiotic susceptibility tests showed high resistance rates to penicillin and erythromycin (95%), moderate resistance rates to cotrimoxazole, doxycycline, clindamycin, and chloramphenicol, and low resistance rates to levofloxacin and ciprofloxacin (5%). Notably, 50% of the isolates were MDR. Among the resistance genes, ermC was most prevalent (87.5%), followed by tetK (80%) and mecA (45%). These findings underscore the widespread presence of S. epidermidis in both healthy and SCM-affected dairy animals, as defined by elevated somatic cell counts, highlighting its dual role as a commensal organism and a potential pathogen, resulting in significant implications for antibiotic resistance management in dairy farming.